Profiles of Social Capital and the Association With Depressive Symptoms Among Multicultural Adolescents in Korea: A Latent Profile Analysis - Eunjoo Kim; Min Kyung Song (Frontiers Media S.A., 2022)
Low social capital has been reported to be associated with depression in adolescents. In general, adolescents with immigrant backgrounds lack social capital. By employing a latent profile analysis (LPA) for the specification of social capital among multicultural adolescents, depression interventions can be explored through the framework of social capital. The purpose of this study was to identify distinct latent profiles of social capital and explore the depressive symptoms of multicultural adolescents in those profiles. Data of 1,244 adolescents from the Multicultural Adolescents Panel Survey (MAPS) were used, which was conducted for 3rd-year middle school students in 2016. An LPA was used to identify profiles by different social capital classes and Quade's non-parametric ANCOVA was used to confirm the differences in depressive symptoms between profiles. Latent profile analysis indicated four classes. Analysis revealed that there were differences in the level of depressive symptoms according to the social capital sub-profiles (F = 44.42, p < 0.001). Class 1 had the lowest level of depressive symptoms (13.91 ± 4.43) and Class 4 had the highest level (18.07 ± 5.25). The depressive symptoms scores of Classes 2 and 3 were 16.49 ± 5.27 and 16.74 ± 4.95, respectively. These findings provide insight into the interplay between social capital and depressive symptoms among multicultural adolescents. Support in consideration of differences in social capital is needed to reduce depression among multicultural adolescents.